2021
DOI: 10.3390/agronomy11020297
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lateral Overturning and Backward Rollover Analysis in a Multi-Purpose Agricultural Machine Developed in South Korea

Abstract: This study analyzed the lateral overturning and backward rollover characteristics of a multi-purpose agricultural machine recently developed in South Korea. Free body diagrams for theoretical analysis and a three-dimensional model for dynamic simulation were created by reflecting the actual dimensions and material properties of the multi-purpose agricultural machine. The simulation model was verified using the minimum turning radius and angle of static falling down sidelong derived through the certified perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The simulation results showed that the average left and right overturning angles decreased by approximately 15 • when a load was applied on the radish collector compared with when no load was applied, and no significant difference in the overturning angle was observed depending on the folded position of the radish collector. Hwang et al [60] determined the critical driving speeds of a tractor that cause lateral overturning and backward rollover based on the internal steering angle and front wheel lift angle and compared them with the results obtained through theoretical equations for lateral overturning and backward rollover. The error between the simulation results and the theoretical equations was found to be less than 5%, and the critical driving speeds of the tractor for lateral overturning and backward rollover decreased as the internal steering angle and front wheel lift angle increased.…”
Section: D Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results showed that the average left and right overturning angles decreased by approximately 15 • when a load was applied on the radish collector compared with when no load was applied, and no significant difference in the overturning angle was observed depending on the folded position of the radish collector. Hwang et al [60] determined the critical driving speeds of a tractor that cause lateral overturning and backward rollover based on the internal steering angle and front wheel lift angle and compared them with the results obtained through theoretical equations for lateral overturning and backward rollover. The error between the simulation results and the theoretical equations was found to be less than 5%, and the critical driving speeds of the tractor for lateral overturning and backward rollover decreased as the internal steering angle and front wheel lift angle increased.…”
Section: D Simulationmentioning
confidence: 99%
“…When attaching the plow, depth should not be excessive The implement should be lifted cautiously As the inner steering angle increases, the safety of the tractor decreases As the front wheel lift angle increases, the safety of the tractor decreases Using weight on the rear wheel located at the top of a slope increases safety [46,52,60] Ground conditions When the ground slope increases, the driving speed must be lowered The higher the obstacle, the lower the safety Maximum coefficient of static friction is the main cause of sideslip The greater the roughness of the ground, the lower the safety The presence of continuous obstacles reduces safety [31,37,46,50,54,57,58,[61][62][63] Recently, the number of studies for developing new models through theoretical analyses and comparing them with simulation results has been increasing. This trend may stem from the considerable time and cost involved in evaluating driving safety by using actual tractors or conducting dynamic experiments, coupled with the high risk of accidents owing to unexpected outcomes.…”
Section: Target Solutions Referencesmentioning
confidence: 99%
“…A 3D model including the main body, front wheels, and rear wheels is produced by reflecting the actual dimensions and physical properties of the original tractor (Figure 4). In addition, the validity of the 3D model is verified by dynamic simulation of the static falling down sidelong angle and minimum turning radius [22]. The 3D model of the original tractor comprises various materials for each component; however, the miniature model is produced using a 3D printer and is made of a single material.…”
Section: Theoretical Analysis Of the Miniature Model's Static Falling...mentioning
confidence: 99%
“…Thus, the risk of accident is not only high but also the efficiency is drastically reduced. In the world, more than 50% of accident that involves death occurs due to lateral overturning and backward rollover of agricultural machines (Hwang, Jang, & Nam, 2021). Even though the demand for power tiller is high but due to the lack of its manoeuvrability on the slope, the usage is reduced (AMC, 2019).…”
Section: Introductionmentioning
confidence: 99%